Pengaruh Gender dan Team Work terhadap Efektivitas Kinerja Karyawan Rumah Sakit Harapan Sehat Meulaboh - Morisna, Titin; Hidayat, Muhammad Rahmat; Rusdi; Damrus; Muzakir (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The performance of hospital employees greatly determines the quality of services provided to patients. Factors that influence the effectiveness of employee performance are gender differences and the ability to work in a team. This research aims at analyzing the effect of gender and teamwork on the effectiveness of employee performance in Harapan Sehat Hospital Meulaboh. This research uses qualitative data that is the respondents’ answers on the research instrument. The population of this research is all employees of Harapan Sehat Hospital Meulaboh which totaling 132 people. This research applies saturated sampling as the technique which means that all the population become the sample of the research. The data analysis is conducted by using partial test (t-test) and simultaneous test (F-test). The results of the study show that: (1) gender has a significant effect on the effectiveness of employee performance; (2) teamwork has a significant effect on the effectiveness of employee performance, and; (3) gender and teamwork simultaneously have a significant effect on the effectiveness of employee performance.